How Followership Boosts Creative Performance as Mediated by Work Autonomy and Creative Self-Efficacy in Higher Education Administrative Jobs - Chiang, Hua-Ling; Lien, Yung-Chih; Lin, An-Pan; Chuang, Ya-Ting (Frontiers in Psychology, 2022)
Followership is an important but understudied domain. This study adopted a follower-centric perspective to examine the internal process by which followership affects creative performance via work autonomy and creative self-efficacy. The study employed a 3-wave survey of 341 employees of a Taiwanese university to achieve the research purpose. This study showed that effective followership (Time 1) is positively associated with employees’ work autonomy (Time 1) and creative self-efficacy (Time 2). Work autonomy and creative self-efficacy mediate the relationship between effective followership and creative performance (Time 3). This study’s empirical findings provide an improved way of measuring followership and broaden our understanding of how followership triggers intrinsic motivation to facilitate creative performance.